Clinical psycho-oncology an international perspective - Grassi, Luigi; Riba, Michelle B. (Wiley-Blackwell, 2012)
"This international primer on psycho-oncology spans settings of care as well as regional boundaries. Designed to be easy to read, with informaton clearly displayed in concise tables and boxes accompanied by clinical vignettes, the book provides clear, practical guidance on all aspects of the psychological care of patients with cancer. Both trainees and practitioners will find it useful in the clinic as well as a resource for continued professional development"--Provided by publisher.